Creating Healthy and Sustainable Buildings An Assessment of Health Risk Factors - Dovjak, Mateja (Springer Nature, 2019)
The open access book discusses human health and wellbeing within the context of built environments. It provides a comprehensive overview of relevant sources of literature and user complaints that clearly demonstrate the consequences of lack of attention to health in current building design and planning. Current designing of energy-efficient buildings is mainly focused on looking at energy problems and not on addressing health. Therefore, even green buildings that place environmental aspects above health issues can be uncomfortable and unhealthy, and can lead to public health problems. The authors identify many health risk factors and their parameters, and the interactions among risk factors and building design elements. They point to the need for public health specialists, engineers and planners to come together and review built environments for human wellbeing and environmental sustainability. The authors therefore present a tool for holistic decision-making processes, leading to short- and long-term benefits for people and their environment.